ANALISIS STANDAR ISI PENDIDIKAN - Sulthanah, Najla; Diniati, Salshabilla; Ramadhani, Irfan; Ananda, Rizki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This article analyzes education policy and management regarding content standards in elementary schools based on Ministerial Regulation No. 21 of 2016 concerning content standards in elementary schools. Based on research conducted through literature review. Content standards are a scope of material that provides experiences for students to learn in order to provide increased knowledge and skills in accordance with environmental needs. Content Standards achieve a comprehensive goal that includes various aspects to be fulfilled as well as being a student learning experience. Education standards in Indonesia have undergone several changes both in the immediate and near future. This shows that the planning and determination of educational standards in Indonesia have not yet been fully developed, it can be seen that many educational standards are not implemented due to frequent changes. Education standards in Indonesia are declared effective if education can produce a generation of the nation that meets current needs. Keywords: content standards and primary schools